Austrian time and marshallian district - on process of location in an out of equilibrium economy - Bruno Lecoq (European Regional Science Association (ERSA), 2002)
The purpose of this paper is to explore the theoretical foundations of marshallian induistrial districts in an "economics of time and ignorance". Industrial districts are disequilibrium and experimental processes. In this contribution, our aim is to link in the same analytical framework the Austrian approach to the temporal structure of production and the Marshallian and Post-Marshallian approach to the growth and organisation of productive knowledge. Our purpose is to understand the processes leading to geographical clustering of firms in terms of temporal coordination of productive activities. Following the Austrian tradition, we suggest that economic geography problems are coordination problems. In this light we argue that the process of location of firms mainly depends on the time dimension of production and innovation interpreted as processes of resources creation and of consequent coordination failures. Eventually we examine the interrelation between different modes of coordinating productive activities ant the territorial organisation of firms. Then a typology of industrial districts in terms of pattern coordination can be proposed. Keywords : Industrial District, out of Equilibrium, Austrian and Marshallian Traditions, Temporal Coordination.
Keywords: 330